ACTN3 R577X Polymorphism Does Not Influence Explosive Leg Muscle Power in Elite Turkish Volleyball Players - (:unkn) unknown (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
The aim of the present study was to evaluate the relationship between explosive power and ACTN3 R577X polymorphism among elite women volleyball players. Voluntary participants (20.88 +/- 3.20 years, 172.72 +/- 9.34 cm, 61.79 +/- 10.08 kg, 20.70 +/- 2.21 kg/m(2)) including elite Turkish women volleyball players (n=72) and nonathletic university students (n=99) were included in the study. Venous blood samples were collected before the jump tests. After anthropometric measurements were obtained, subjects performed static vertical jump and counter movement jump to evalute explosive power performances. ACTN3 R577X polymorphism analyses were assessed on the blood samples in order to evaluate the genotypic frequencies of the ACTN3 R577X genotypes differed between groups. There was no statistically significant difference on ACTN3 R577X polymorphism groups' genotype distribution in the study groups. The genotype distribution was similar for both volleyball players and the nonathletic university students (p= 0.77). Moreover, there was no statistically significant difference for vertical and counter jump results on ACTN3 R577X polymorphism RR, RX and XX genotypes for volleyball players and the nonathletic university students. As a conclusion, the findings of the study reveal that ACTN3 R577X polymorphism has a key role in explaining individual phenotypic differences in muscle strength, but not affecting volleyball performance singly at least for elite Turkish women volleyball players. In addition, it is believed that this polymorphism are not strong enough to be predictive or/and utilized seperately as a talent identification factor in volleyball.
Keywords: ACTN3; Volleyball; Explosive power; GENOTYPE; ASSOCIATION; PERFORMANCE; STRENGTH; ALPHA-ACTININ-3; PHENOTYPES; GENE; ACE; EVOLUTION; ENDURANCE